How many positive integers x satisfy the equation below?
⌈ 4 x ⌉ + 9 = ⌊ x ⌋
Notations:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L e t f ( X ) = 9 − ⌊ X . 5 ⌋ + ⌈ X . 2 5 ⌉ . . . . . . . . ∴ f o r f ( X ) = 0 , . . . . . . . . . . . . . X . 5 > 9 , ⟹ X > 8 1 . 8 1 . 2 5 = 3 , . . . . . . S o X > ( 9 + 3 ) 2 = 1 4 4 = 1 2 2 . . L e t X = 1 3 2 = 1 6 9 . ∴ f ( 1 6 9 ) = 9 − ⌊ 1 6 9 . 5 ⌋ + ⌈ ( 1 6 9 ) . 2 5 ⌉ = 9 − 1 3 + ⌈ 3 . 7 . . ⌉ = 9 − 1 3 + 4 = 0 . W h e n ⌊ X . 5 ⌋ = 1 4 , f ( 1 4 ) > 0 . 1 4 2 = 1 9 6 . S o f o r X f r o m 1 6 9 t o 1 9 6 − 1 = 1 9 5 , w e w i l l g e t f ( X ) = 0 . ∴ N u m b e r o f s o l u t i o n s = 1 9 5 − 1 6 9 + 1 = 2 7 .
Problem Loading...
Note Loading...
Set Loading...
Let , x = a 4 + k where, a 4 ≤ a 4 + k < ( a + 1 ) 4 and, a and k are integer.
a 4 ≤ a 4 + k < ( a + 1 ) 4 a 4 ≤ x < ( a + 1 ) 4 a 2 ≤ x < ( a + 1 ) 2 a 2 ≤ ⌊ x ⌋ < ( a + 1 ) 2
Again,
a 4 ≤ a 4 + k < ( a + 1 ) 4 a 4 ≤ x < ( a + 1 ) 4 a ≤ 4 x < ( a + 1 )
So, a = 4 x or a < 4 x < ( a + 1 )
If, a = 4 x Then, ⌈ 4 x ⌉ + 9 = ⌊ x ⌋ a + 9 = a 2
solving the equation we get , a = 2 1 ± 3 7 which is not an integer.
So, it should be , a < 4 x < ( a + 1 ) , therefore ⌈ 4 x ⌉ = ( a + 1 )
If, a 2 ≤ ⌊ x ⌋ we get ,
\begin{aligned}\lceil \sqrt[4]{x} \rceil+9&=\lfloor\sqrt{x}\rfloor\\a+1+9&\ge a^2\\\frac{1-\sqrt{41}}{2}&\le a\le \frac{1+\sqrt{41}}{2}\\-1&\le a\le 3\tag{1}\end{aligned}
If, ( a + 1 ) 2 > ⌊ x ⌋ we get ,
\begin{aligned}\lceil \sqrt[4]{x} \rceil+9&=\lfloor\sqrt{x}\rfloor\\a+1+9&< a^2+2a+1\\\frac{-1-\sqrt{37}}{2}&\ge a \hspace{1cm}or, \hspace{1cm}\frac{-1+\sqrt{37}}{2}<a\\-3&> a\hspace{1cm} or,\hspace{1cm} 3<a\tag{2}\end{aligned}
Solving (1) and (2) we get, a = 3
Let , ⌊ x ⌋ = a 2 + s , where s is an integer and , 0 ≤ s ≤ 2 a
⌈ 4 x ⌉ + 9 a + 1 + 9 3 + 1 + 9 s = ⌊ x ⌋ = a 2 + s = 3 2 + s = 4
Therefore,
⌊ x ⌋ 1 3 2 1 6 9 1 6 9 = a 2 + s = 3 2 + 4 = 1 3 ≤ x < ( 1 3 + 1 ) 2 ≤ x < 1 9 6 ≤ x ≤ 1 9 5
So , there are 1 9 5 − 1 6 9 + 1 = 2 7 positive integers that satisfy the equation .